2012
DOI: 10.1152/japplphysiol.00553.2012
|View full text |Cite
|
Sign up to set email alerts
|

Central neuromodulatory pathways regulating sympathetic activity in hypertension

Abstract: The classical neurotransmitters, glutamate and GABA, mediate fast (milliseconds) synaptic transmission and modulate its effectiveness through slow (seconds to minutes) signaling processes. Angiotensinergic pathways, from the lamina terminalis to the paraventricular nucleus (PVN)/supraoptic nucleus and rostral ventrolateral medulla (RVLM), are activated by stimuli such as circulating angiotensin type II (Ang II), cerebrospinal fluid (CSF) sodium ion concentration ([Na(+)]), and possibly plasma aldosterone, lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
76
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(78 citation statements)
references
References 122 publications
0
76
0
2
Order By: Relevance
“…In addition, excessive dietary salt intake by humans has been strongly implicated in the development of heart, renal and liver failure, as well as salt-sensitive hypertension Gabor and Leenen, 2012).…”
Section: General Introduction Thirst and Salt Appetite Are Controlledmentioning
confidence: 99%
“…In addition, excessive dietary salt intake by humans has been strongly implicated in the development of heart, renal and liver failure, as well as salt-sensitive hypertension Gabor and Leenen, 2012).…”
Section: General Introduction Thirst and Salt Appetite Are Controlledmentioning
confidence: 99%
“…Reversal of genomic effects of MR activation takes time, and time is also needed to reverse activation of downstream signaling mechanisms associated with the slow aldosterone-MR-EO pathway in the CNS. 34 …”
Section: Intracerebroventricular Infusion Of Eplerenonementioning
confidence: 99%
“…Pharmacological inhibition of Mc4r in adult rats reduces the obesity-related hypertension and renal sympathetic nerve activity (RSNA) associated with hyperleptinemia (7,8). Moreover, the highest expression of hypothalamic Mc4r mRNA is found in the paraventricular nucleus of the hypothalamus (PVH), which integrates and responds to a variety of neural and humoral signals regulating RSNA (9)(10)(11)(12). It has been shown that leptin stimulates the tonic firing rate of Mc4r PVH neurons in rats, resulting in heightened arterial pressure, a finding that is consistent with causal links between obesity and adult hypertension (13).…”
mentioning
confidence: 99%